2009
DOI: 10.1203/pdr.0b013e3181961d2a
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Features With the Mutational Status of GM-CSF Signaling Pathway-Related Genes in Juvenile Myelomonocytic Leukemia

Abstract: Mutations in RAS, neurofibromatosis type 1 (NF1), and PTPN11, constituents of the granulocyte-macrophage colonystimulating factor signaling pathway, have been recognized in patients with juvenile myelomonocytic leukemia (JMML). We assessed 71 children with JMML for NRAS, KRAS, and PTPN11 mutations and evaluated their clinical significance. Of the 71 patients, three had been clinically diagnosed with neurofibromatosis type 1, and PTPN11 and NRAS/KRAS mutations were found in 32 (45%) and 13 (18%) patients, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 28 publications
3
66
0
3
Order By: Relevance
“…The association of PTPN11 mutation with RASA4 TSS2 methylation is compatible with the observation that PTPN11-mutant cases tend to run a more aggressive clinical course. 11,12 Conversely, there was only one patient with CBL alteration among 42 in the highest methylation tertile, but 8 CBL-mutant cases out of 42 in the lowest tertile (P = 0.04, chi-square test). A recent exome-wide sequencing study identified mutations in SETBP1 and JAK3 as genetic lesions in JMML with probable prognostic impact, but information on these mutations was unavailable in our cohort, precluding a comparison with RASA4 methylation.…”
Section: Hypermethylation Of Rasa4 Is Associated With Specific Genetimentioning
confidence: 96%
See 1 more Smart Citation
“…The association of PTPN11 mutation with RASA4 TSS2 methylation is compatible with the observation that PTPN11-mutant cases tend to run a more aggressive clinical course. 11,12 Conversely, there was only one patient with CBL alteration among 42 in the highest methylation tertile, but 8 CBL-mutant cases out of 42 in the lowest tertile (P = 0.04, chi-square test). A recent exome-wide sequencing study identified mutations in SETBP1 and JAK3 as genetic lesions in JMML with probable prognostic impact, but information on these mutations was unavailable in our cohort, precluding a comparison with RASA4 methylation.…”
Section: Hypermethylation Of Rasa4 Is Associated With Specific Genetimentioning
confidence: 96%
“…[5][6][7][8][9] Although these mutations are thought to represent the cardinal genetic feature of JMML, it is still unclear if and how they determine treatment resistance. [10][11][12] Additional genetic changes frequently observed in JMML include chromosomal aberrations, most notably monosomy 7, which is detected in approximately 25% of cases. 1,13 We recently reported that the strongest prognostic factor on the molecular level is neither Ras pathway mutation nor karyotype but the presence of DNA hypermethylation at several target genes, 4 suggesting an important role of epigenetic events in the pathobiology of resistant JMML.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors include older age at diagnosis (Ͼ2 years), increased fetal hemoglobin for age (Hgb F), and/or a platelet count under 33,000/uL at presentation, as well as female sex in some studies. 34 37 In their study, mutation of PTPN11 was associated with older age at diagnosis (Ͼ24 months), increased Hgb F (Ͼ10%), reduced overall survival, and, importantly, appeared to be an unfavorable prognostic factor predicting relapse following transplantation.…”
Section: Pediatric Malignanciesmentioning
confidence: 96%
“…In JMML, these somatic gain-of-function mutations occur in NRAS and KRAS and are found in leukemic cells at diagnosis in 20-25% of cases. 44,50,51,63 Rarely, insertions are noted. 64 For both, NRAS-and KRAS-associated disease, acquired loss…”
Section: Juvenile Myelomonocytic Leukemia With Somatic Ras Mutationsmentioning
confidence: 99%
“…Mutations were often subclonal and were involved in the progression of leukemia.82 Genetic alterations in SRFS2, TET2, RUNX1, JAK2 and ASXL1 do not play a significant role in JMML. 51,75,[83][84][85][86] Similarly, inactivation of the TP53 tumor suppressor gene and internal tandem duplication and activation of the Fms-like tyrosine kinase 3 (FLT3) gene are generally absent in JMML. 87,88 With the paucity of genetic lesions, epigenetic changes such as abnormal DNA methylation pattern are of particular interest.…”
Section: Other Genetic and Epigenetic Lesions In Juvenile Myelomonocymentioning
confidence: 99%